Role of Control Mechanisms in Internal SCM and Quality Performance: Risk Management in Supply Chain Management - Jetsalid Anesukanjanakul; Komkrit Rattamanee (International Journal of Supply Chain Management, 2019)
The current study aims to assess the role of control mechanism in supply chain management and quality performance of the firms. For this purpose, the current study examines the impact of two control mechanisms named as â€œformal controlâ€ and â€œsocial controlâ€ on the internal supply chain management (SCM) of the firm. Furthermore, the current study investigates the influence caused by internal SCM on quality performance of the firm. To accomplish the objectives of the current study. The data was collected from 294 manufacturers of Thailand through questionnaire based survey study. The quantitative research methods was used to collect data about the formal control, social control, internal SCM and quality performance of the firm and the collected data was then put into analysis through SPSS and AMOS in which different key tests were applied to reach the acceptance or rejection of hypotheses. It is found through current study that control mechanisms have positive influence on internal SCM because the social control and formal control showed significant positive influence on internal SCM. It is further found in the current study that internal SCM has significant positive influence on quality performance so, the improved and effective internal SCM tends to enhance the quality performance of the firm. The current study has important implications in literature and practice due to its significant contributions.